2021
DOI: 10.1038/s41598-021-83510-8
|View full text |Cite
|
Sign up to set email alerts
|

Binocular summation is affected by crowding and tagging

Abstract: In perceptual crowding, a letter easily recognized on its own, becomes unrecognizable if it is surrounded by other letters, an effect that confers a limit on the visual processing. Models assume that crowding is a hallmark of the periphery but that it is almost absent in the fovea. However, recently it was shown that crowding occurs in the fovea of people with an abnormal development of functional vision (amblyopia), when the stimulus is presented for a very short time. When targets and flankers are dissimilar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 73 publications
(51 reference statements)
4
4
0
Order By: Relevance
“…Our findings showed that the glaucomatous vision did not exhibit binocular summation of crowding as the binocular crowding was determined by the better eye. This absence of binocular summation is consistent with a previous study done by Siman-Tov et al 68 …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Our findings showed that the glaucomatous vision did not exhibit binocular summation of crowding as the binocular crowding was determined by the better eye. This absence of binocular summation is consistent with a previous study done by Siman-Tov et al 68 …”
Section: Discussionsupporting
confidence: 94%
“…Our findings are consistent with the view that glaucomatous damage brings about alterations in spatial pooling mechanisms. Furthermore, the absence of binocular summation for crowding observed in glaucomatous vision combined with the lack of binocular summation found in Siman-Tov et al's 68 normal healthy vision support the view that crowding may start in the early stages of visual processing, at least before the process of binocular integration takes place.…”
Section: Discussionmentioning
confidence: 56%
“…Taken together, these findings support our conclusion that the binocular summation mechanism is resilient in glaucoma. [36][37][38][39] Interestingly, we did not find any meaningful relationships between stereoacuity and binocular summation for both groups, supporting the view that the 2 pathways do not overlap. However, patients included in this study were specifically selected to have very early-stage glaucoma, no significant asymmetry in clinical measures between their right and left eyes, and the median stereopsis was within the normal population range.…”
Section: Discussionsupporting
confidence: 56%
“…Small stereoscopic disparity differences between target and flankers create differences in perceived depth that can alleviate the effects of crowding, potentially through grouping (Herzog and Manassi, 2015) or by independent processing of target and flankers in different depth-selective channels (Norcia et al, 1985; Pulliam, 1981; Reynaud and Hess, 2017; Tyler et al, 1994; Wilcox and Allison, 2009; Yang and Blake, 1991) by any of the computational models of crowding based on texture processing (Balas et al, 2009; Freeman and Simoncelli, 2011; Parkes et al, 2001; Wallis and Bex, 2012), sampling errors (Ester et al, 2015, 2014; Harrison and Bex, 2017, 2016, 2015) attentional resolution limits (He et al, 1996) or saccade properties (Nandy and Tjan, 2012). Large interocular disparity differences may induce diplopia or suppression that could increase perceptual error by increasing the number of features (diplopia) or removing the benefit of binocular summation (suppression) that can help decrease the effects of crowding (Siman-Tov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted November 28, 2022. ; https://doi.org/10.1101/2022.11.23.517719 doi: bioRxiv preprint benefit of binocular summation (suppression) that can help decrease the effects of crowding (Siman-Tov et al, 2021).…”
Section: Author Contributionsmentioning
confidence: 99%